Laparoscopic subperitoneal injection of chemo-loaded particles lowers tumor growth on a rabbit model of peritoneal carcinomatosis - Florentina Pascale; Afshin Fazel; Julien Namur; Saida-Homayra Ghegediban; Hadrian D’Inca; Michel Wassef; Laurence Moine; Alexandre Laurent (Tumor Biology)
The purpose of our study was to assess the effect of controlled-release chemotherapy on the growth and viability of peritoneal carcinomatosis treated by subperitoneal injection in a rabbit VX2 model. A model of peritoneal carcinomatosis was created by laparoscopic injection of VX2 tumor in the left and right broad ligaments of 12 White New Zealand rabbits. At day 12, each tumor was randomly treated with a peritumoral injection of 0.5 mL microspheres loaded with doxorubicin (DEM-DOX) or unloaded (DEM-BLAND). Seven days after treatment, tumor volume, tumor viability in histology, local tumor necrosis in contact with DEM, and doxorubicin concentration profile around the drug eluting microspheres (DEM) were measured. Tumor volume was significantly lower in the DEM-DOX group (3.6 ± 3.2 cm 3 ) compared with the DEM-BLAND group (8.9 ± 5.4 cm 3 ) (p = 0.0425). The percentage of viable tumor tissue was significantly lower in the DEM-DOX group (38% ± 17%) compared with the DEM-BLAND group (56% ± 20%) (p = 0.0202). Tissue necrosis was observed around all DEM-DOX up to a distance of 1.094 ± 0.852 mm and never observed around DEM-BLAND. Drug concentration was above the therapeutic level of 1.0 µM up to a distance of 1.4 mm from the DEM to the tumor. Laparoscopic subperitoneal injection of chemo-loaded particles is feasible and lowers tumor growth and viability in a rabbit model of peritoneal carcinomatosis after 1 week.